A different way of teaching the reflection of light: Using the clock model. (2nd October 2018) - Cengiz, Ekrem
Abstract: The goal of this study is to present and evaluate a different way of teaching concepts related to the reflection of light (incident beam, reflecting beam, angle of incidence, angle of reflection, surface, regular reflection, and diffuse reflection). The participants were 42 sixth-grade students (between the ages of 11 and 12) attending a public middle school in the eastern region of Turkey. Students were given the opportunity to learn concepts related to reflection while performing experiments and making observations on their own with a mirror and clock model created by the teacher. The study enabled students to learn about the subject of reflection in a meaningful way, showing a full grasp of the concepts based on both interviews and students worksheets. The implications of these results could help teachers to support students' learning of concepts related to light based on the exhibited benefits of using a clock model.